Visitors’ perceptions towards the sustainable use of forest areas: the case of Istanbul Belgrade nature parks - Yıldırım, Hasan Tezcan (2024)
The main purpose of this study is to analyze how stakeholders’ perceptions of sustainable land use and the management of natural parks affect land management planning, with a focus on park visitors. This study was carried out in July 2019, during a period of high visitor numbers at the Belgrade Forest nature parks, as reported by the park manager. It involved evaluating participants’ knowledge about the specific natural park they visit and the organization managing it. The results show that the mode of transportation significantly influences this knowledge. Visitors who walked or drove to the park demonstrated a greater understanding of the park and its management. A visit to a nature park typically involves anticipation, planning, the visit itself, participating in activities, returning, and reflecting on past experiences. Visitors are drawn to the Belgrade Forest nature parks because of their cleanliness, family-friendly atmosphere, peacefulness, proximity, uniqueness as a green space in Istanbul, wooded areas, and suitability for sports. The study also reveals that the characteristics of nature parks, such as park amenities, distance, transportation options, and reasons for visiting, contribute to visitors’ happiness, especially affecting younger visitors between the ages of 19 and 30. These findings highlight the varied nature of visitors’ impressions after their visit, depending on their individual characteristics. In conclusion, this detailed analysis offers valuable insights to guide strategic park management efforts aimed at promoting sustainability and enhancing visitor experiences in the Belgrade Forest areas of Türkiye.